Polylactic Acid (PLA) Composite Films Reinforced with Wet Milled Jute Nanofibers. (21st November 2013) - Baheti, Vijay; Militky, Jiri; Ul Hassan, S. Z.
Abstract : In the present study, waste jute fibers formed in textile industries were wet pulverized to nanoscale using high energy planetary ball milling. The rate of refinement of uncleaned jute fibers having noncellulosic contents was found slower than the cleaned jute fibers. This behavior is attributed to the strong holding of fiber bundles by noncellulosic contents which offered resistance to the defibrillation during wet milling. In addition, the pulverization of fibers in the presence of water prevents the increase in temperature of mill which subsequently avoided the sticking of material on the milling container. After three hours milling, the diameter of nanofibers was observed around 50 nm. In the further stage, obtained nanofibers were incorporated under 1 wt%, 5 wt%, and 10 wt% loading into polylactic acid composite films. The potentials of jute nanofibers were investigated for improvement in mechanical and barrier properties of films. The maximum improvement in mechanical properties was observed in case of 5 wt% composite film where Young's modulus was increased to 3.3 GPa from 1.0 GPa as compared with neat PLA film.